At the Old Haunted House - Ketteman, Helen; Wragg, Nate (New York : Two Lions, 2014)
Many creatures live at the old haunted house with their children, including one small witch, two little monsters, three kittens, four goblins, five werewolves and more. When the neighborhood children come trick-or-treating, they are invited inside for a fun party with all.
Keywords: Halloween -- Juvenile fiction; Haunted houses -- Juvenile fiction; Counting -- Juvenile fiction; Halloween -- Fiction; Haunted houses -- Fiction; Stories in rhyme